The effect of health on refugees’ labor market integration: Evidence from a natural experiment in Germany - Laura Goßner; Philipp Jaschke; Yuliya Kosyakova (PLoS ONE, 2026)
This paper analyzes the role of health for refugees’ integration into host countries’ labor markets. We exploit the quasi-random dispersal policies of refugees across regions in Germany to analyze the causal effect of health on employment. Based on regional and temporal heterogeneity in a policy adoption that provided earlier access to healthcare services through electronic health cards (eHCs), combined with the regional availability of healthcare services and pre-migration health status, we construct instrumental variables (IVs) providing plausibly exogenous variation in refugees’ post-arrival health status. Our results reveal that favorable physical health (PCS) improves refugees’ employment probability. Favorable mental health (MCS) increases only females’ employment rates, although this effect must be scrutinized due to weak instruments. Regarding potential mechanisms, we provide evidence that better health increases language course participation and German language proficiency for female refugees.